Spirit-Quieting Traditional Chinese Medicine May Improve Survival in Prostate Cancer Patients with Depression - Lin, Po-Hung (J Clin Med, 2019)
Depression is associated with higher mortality in prostate cancer. However, whether traditional Chinese medicine (TCM) for depression improves outcomes in patients with prostate cancer is unclear. This retrospective cohort study evaluated the association between TCM for depression and mortality in patients with prostate cancer. During the period 1998–2012, a total of 248 prostate cancer patients in Taiwan with depression were enrolled and divided into three groups: TCM for depression (n = 81, 32.7%), TCM for other purposes (n = 53, 21.3%), and no TCM (n = 114, 46.0%). During a median follow-up of 6.2 years, 12 (14.8%), 13 (24.5%), and 36 (31.6%) deaths occurred in the TCM for depression, TCM for other purposes, and no TCM groups, respectively. After adjusting age at diagnosis, urbanization, insured amount, comorbidity disease, and prostate cancer type, TCM for depression was associated with a significantly lower risk of overall mortality based on a multivariate-adjusted Cox proportional-hazards model (hazard ratio 0.42, 95% confidence interval: 0.21–0.85, p = 0.02) and Kaplan–Meier survival curve (log-rank test, p = 0.0055) compared to no TCM. In conclusion, TCM for depression may have a positive association with the survival of prostate cancer patients with depression.